Risk of intracranial haemorrhage in antidepressant users with concurrent use of non-steroidal anti-inflammatory drugs: nationwide propensity score matched study - Shin, Ju-Young (BMJ, 2015)
Objective To define the risk of intracranial haemorrhage among patients treated with antidepressants and non-steroid anti-inflammatory drugs (NSAIDs), compared with the risk among those treated with antidepressants without NSAIDs. Design Retrospective nationwide propensity score matched cohort study. Setting Korean nationwide health insurance database between 1 January 2009 and 31 December 2013. Participants Patients who began receiving antidepressants for the first time (index date) without a history of having received a prescription for antidepressants during the preceding year. Patients who had been diagnosed as having cerebrovascular diseases within a year before the index date were excluded. Main outcome measure Time to first hospital admission with intracranial haemorrhage within 30 days after drug use. Matched Cox regression models were used to compare the risk of intracranial haemorrhage among patients who were treated with antidepressants with and without NSAIDs, after propensity score matching with a 1:1 ratio. Results After propensity score estimation and matching in a 1:1 ratio, the cohort used in the analysis included 4 145 226 people. The 30 day risk of intracranial haemorrhage during the entire study period was higher for combined use of antidepressants and NSAIDs than for use of antidepressants without NSAIDs (hazard ratio 1.6, 95% confidence interval 1.32 to 1.85). No statistically meaningful differences were found in risk of intracranial haemorrhage between the antidepressant drug classes. Conclusions Combined use of antidepressants and NSAIDs was associated with an increased risk of intracranial haemorrhage within 30 days of initial combination.